2008
DOI: 10.1001/archneur.65.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Spastic Paraplegia With Mental Impairment and Thin Corpus Callosum in Tunisia

Abstract: To perform a clinical and genetic study of Tunisian families with autosomal recessive (AR) hereditary spastic paraplegia with thin corpus callosum (HSP-TCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 27 publications
5
62
0
1
Order By: Relevance
“…Similar to other communities with high consanguinity, 9,10 we found that AR HSP inheritance is predominant in Sudan. However, in our series, the complex phenotype is predominant (84%), which is in disagreement with Coutinho et al 9 who elicited a predominant pure phenotype, but in agreement with a study in South Tunisia 10 that reported 69% of complex cases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to other communities with high consanguinity, 9,10 we found that AR HSP inheritance is predominant in Sudan. However, in our series, the complex phenotype is predominant (84%), which is in disagreement with Coutinho et al 9 who elicited a predominant pure phenotype, but in agreement with a study in South Tunisia 10 that reported 69% of complex cases.…”
Section: Discussionsupporting
confidence: 87%
“…8 On the contrary, AR HSP predominates in highly consanguineous communities. 7,9,10 Thin corpus callosum-associated HSP (TCC-HSP) represents a distinct subgroup accounting for approximately one-third of all AR HSP. 11 At least nine genes have been identified to be responsible for TCC-HSP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed mutations recurring in several ethnicities. As an example, we found the frequent homozygous c.6100C>T (p.R2034X), already detected in northern African families Stevanin et al 2008a;Boukhris et al 2008a), in one Brazilian kindred with partially common haplotypes (see Table 2). Similarly, the c.529_533del5 (p.I177_F178del>S177fsX) mutation, already reported in three Portuguese families Stevanin et al 2008a), was also detected in an additional Brazilian family again segregating with a similar disease-bearing chromosome.…”
Section: Spg11 Mutation Screeningmentioning
confidence: 55%
“…Together with the already reported changes Del Bo et al 2007;Hehr et al 2007;Boukhris et al 2008a;Paisan-Ruiz et al 2008;Zhang et al2008;Lee et al 2008;Erichsen et al 2008), disease-associated mutations in SPG11 are now 67 and almost invariably alter the correct formation of a complete protein product in all except one case. If formed, the protein would be rapidly degraded or significantly shortened.…”
Section: Discussionmentioning
confidence: 76%